2007
DOI: 10.1243/09576509jpe219
|View full text |Cite
|
Sign up to set email alerts
|

Use of fuchsine basic: Ethylenediaminetetraacetic acid system in photogalvanic cell for solar energy conversion

Abstract: Fuchsine basic has been used as a photosensitizer in photogalvanic cell for solar energy conversion. Ethylenedianinetetraacetic acid was used as an electron donor. The photopotential and photocurrent generated by this cell were 650.0 mV and 60.0 mA, respectively. The effects of various parameters, such as pH, light intensity, diffusion length, reductant concentration, dye concentration, etc. on the electrical output of the cell has been studied. The current -voltage (i-V) characteristics of the cell have also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…To put this suggestion into application, various studies on photo-galvanic cell systems have been reported. The use of various dye photo-sensitizers, such as thionine, 3 methylene blue, 4 thionine-loaded Naon lm, 5 bromophenol red, 6 fuchsine basic, 7 Congo red, 8 azure A, 10 and malachite green; 11 various inorganic and organic reductants, such as iron, 3 ethylenediamine tetraacetate-EDTA, 6-8 ascorbic acid, 10 and arabinose; 10 and various surfactants, such as NaLS, 10,11 Tween-80, 13 diethylenetriaminepentaacetic acid (DPTA), 17 and dioctylsulphosuccinate (DSS) 20 have been reported for solar energy and conversion through PG cells. A literature survey reveals that the main fabrication components of PG cells are an anodic electrode (Pt), cathodic electrode (saturated calomel electrode-SCE), sensitizer(s), reductant(s), NaOH, H-shaped glass tubes, etc., and the optimum electrical cell performance is dependent on variables such as concentration (of the sensitizer, reductant, surfactant, and NaOH, i.e., pH), diffusion length, electrodes, electrode kinetics, diffusion, external load, illumination intensity, and temperature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To put this suggestion into application, various studies on photo-galvanic cell systems have been reported. The use of various dye photo-sensitizers, such as thionine, 3 methylene blue, 4 thionine-loaded Naon lm, 5 bromophenol red, 6 fuchsine basic, 7 Congo red, 8 azure A, 10 and malachite green; 11 various inorganic and organic reductants, such as iron, 3 ethylenediamine tetraacetate-EDTA, 6-8 ascorbic acid, 10 and arabinose; 10 and various surfactants, such as NaLS, 10,11 Tween-80, 13 diethylenetriaminepentaacetic acid (DPTA), 17 and dioctylsulphosuccinate (DSS) 20 have been reported for solar energy and conversion through PG cells. A literature survey reveals that the main fabrication components of PG cells are an anodic electrode (Pt), cathodic electrode (saturated calomel electrode-SCE), sensitizer(s), reductant(s), NaOH, H-shaped glass tubes, etc., and the optimum electrical cell performance is dependent on variables such as concentration (of the sensitizer, reductant, surfactant, and NaOH, i.e., pH), diffusion length, electrodes, electrode kinetics, diffusion, external load, illumination intensity, and temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Anionic surfactants are reported to be the most effective surfactants for solar power and storage through PG cells. 7,26 In view of these facts, a metanil yellow-formic acid-sodium lauryl sulfate (SLS)-NaOH chemical system along with a small Pt electrode and SCE component of the combination electrode has been used to further enhance the electrical output of PG cells at low intensity. At optimal values of the cell fabrication variables, the i-V characteristics of the cell show that the highest power (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Photogalvanic cells are a photoelectrochemical device in which solar energy convert into electrical energy via formation of energy rich species that exhibit the photogalvanic effect. The photogalvanic effect was first of all recognized by Rideal and Williams [1] and it was systematically studied by Rabinowitch [2][3], and then by other workers [4][5][6][7][8][9]. Some researchers [10][11] have studied on how to enhance the performance and optimum efficiency of dye sensitized solar cell for solar energy conversion.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, this field of research has been contributed to by Genwa and Genwa (2008), Genwa and Khatri (2006), Madhwani et al (2007), Ameta et al (2007), Kumari et al (2009), Pokhrel andNagaraja (2009), Gangotri and Gangotri (2009a, b) and Gangotri and Bhimwal (2010a, b). They have used different reductants, photosensitizers and surfactants to investigate interesting photogalvanic systems to enhance conversion efficiency and storage together with the effect to reduce the cost of construction and to ensure commercial viability.…”
Section: Introductionmentioning
confidence: 99%